2019
DOI: 10.21129/nerve.2019.5.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Craniofacial Pain from Entrapment of the Greater Occipital Nerve Misdiagnosed as Chronic Migraine, Idiopathic Odontalgia, and Atypical Facial Pain

Abstract: Although the cause of occipital neuralgia is mostly unknown, entrapment of the greater occipital nerve (GON) at its piercing point of the tendinous aponeurotic attachment of the trapezius at the superior nuchal line has been reported to be the most common cause. We report an occurrence of unilateral facial pain associated with continuous aching and stabbing headache in the frontotemporal and occipital regions in a patient whose occipital neuralgia has lasted for years. These symptoms were completely different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Although it has been suggested that the pain of occipital neuralgia can reach the frontoorbital (V1) area through trigeminocervical interneuronal connections in the trigeminal spinal nucleus [1], reports of referred trigeminal pain from occipital neuralgia are rare [2]. However, recently, pain referred to the facial trigeminal nerve distribution by occipital neuralgia due to GON entrapment has been reported [2][3][4][5]. Referral to the facial trigeminal distribution occurred not only in the V1 region but also in the V2 and V3 regions and even caused hemifacial sensory changes [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it has been suggested that the pain of occipital neuralgia can reach the frontoorbital (V1) area through trigeminocervical interneuronal connections in the trigeminal spinal nucleus [1], reports of referred trigeminal pain from occipital neuralgia are rare [2]. However, recently, pain referred to the facial trigeminal nerve distribution by occipital neuralgia due to GON entrapment has been reported [2][3][4][5]. Referral to the facial trigeminal distribution occurred not only in the V1 region but also in the V2 and V3 regions and even caused hemifacial sensory changes [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…ese aspects made the diagnosis very difficult. e natural course of untreated occipital neuralgia due to chronic entrapment of the GON remains unknown [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations